Effect of the ‘Bijak Garam’ meal program on nutrient intake, frailty, biomarkers, and quality of life in older adults - Toto Sudargo; Nida Amira Taris Yolanda; Esmeralda Cantika Rachma; Wanda Azka Atsiila; Jennifer Yapita; Ali Rosidi; Yuliana Noor Setiawati Ulvie; Aripin Ahmad (AcTion: Aceh Nutrition Journal, 2025)
Older adults are a vulnerable group prone to degenerative diseases and decline in quality of life, often characterized by geriatric syndromes such as frailty. Nutritional intervention plays an important role in addressing these challenges. However, evidence of the effectiveness of dietary programs combined with structured nutrition education in nursing homes remains limited. This study aimed to evaluate the “Bijak Garam” program, a combination of a low-salt diet and nutrition education, on the dietary intake, blood biomarkers, physical function, and health status of older adults. A quasi-experimental study was conducted using a pre-post, one-group design with purposive sampling involving 100 participants. Dietary intake was assessed using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), physical function was measured using handgrip strength and the FRAIL scale, and blood biomarkers were analyzed using standard laboratory methods. Data were analyzed using paired t-test or Wilcoxon signed-rank test. The Bijak Garam intervention effectively improved dietary intake and reduced HbA1c, total cholesterol, LDL, triglyceride, and diastolic blood pressure (p < 0,05), while HDL levels increased significantly (p < 0,05). Most of the participants preferred plant-based protein sources. These findings demonstrate that the Bijak Garam program can improve dietary patterns and several health indicators among older adults, with the potential to be implemented more widely in geriatric nutritional interventions and public health policies.